Inside the Bank of England - Hobday, Peter; Long, James William Davenport (Hove : Priory Press, 1976)
The Governor of the Bank is one of the most powerful men in Britain. Yet you hardly see him on television or read about him in the papers. Few people really know what goes on inside the Bank.
Includes index.
Bibliography: p. 78.
osc 22/08/17
Loans
Keywords: Money